Pemetaan Tren: Analisis Bibliometrik dari Audit Report Lag yang Terindex Google Schoolar - Aisyah Kamila Putri; Sri Andriani; Ahmad Fahrudin Alamsyah (AKUA: Jurnal Akuntansi dan Keuangan, 2024)
Financial reports are an important thing that is really needed by a company. The audit assessment has an impact on the financial reports that will be published. The study of audit delays is experiencing rapid growth. This has attracted the interest of many researchers to continue developing it, including analyzing internal and external company factors that influence audit delays. However, until now, publications related to this topic have not been well organized. This research aims to map research publications related to audit delays in a database context, with the keyword "audit delays" with the VOSviewer Bibliometric research study. The analytical method used is a quantitative method. Data sources were taken from journals indexed by Google Scholar, Sinta, and Emerald, then analyzed with the help of Publish or Perish and Mendeley Desktop software to screen the data. The results of this research show that in the Vosviewer Bibliometric study there are 3 Clusters and 24 main topics related to Audit Report Lag. This research provides an overview of relevant topic mapping for further research.